Numerical Investigation of the Effects of Aquatic Vegetation on Wind-Induced Wave and Current Characteristics in Shallow Lakes - Wu, Chenhui; Wu, Shiqiang; Wu, Xiufeng; Dai, Jiangyu; Gao, Ang; Yang, Fan (Frontiers in Environmental Science, 2022)
Aquatic vegetation is one of the important parts of shallow lake ecosystem, which has an important impact on the characteristics of wind-driven wave and current. In this paper, we embed the vegetation module into the flow model TELEMAC-3D and the wave model TOMAWAC respectively, and construct the coupling model of flow-wave-vegetation in the open source model Open Telemac-Mascaret. Through the verification of two sets of experimental data, it is proved that the model can well reproduce the influence of vegetation on current and wave. Then, the model is applied to the wind-driven wave and current simulation of a typical shallow lake, Taihu Lake. The results show that the model can accurately reproduce the characteristics of wind-driven wave and current. Aquatic vegetation significantly changes the velocity, wave height and local three-dimensional circulation flow in the vegetation patches. At the same time, the existence of aquatic vegetation reduces the material exchange rate between the vegetation area and the outside world, which has a significant impact on the material transport characteristics of the lake. Sensitivity analysis shows that the influence of aquatic vegetation should not be ignored in the simulation of wind-induced wave current and material transport in shallow lakes.